In vivo toxicity assessment of non-cadmium quantum dots in BALB/c mice - Lin, Guimiao; Ouyang, Qingling; Hu, Rui; Ding, Zhangchi; Tian, Jinglin; Yin, Feng; Xu, Gaixia; Chen, Qiang; Wang, Xiaomei; Yong, Ken-Tye (Nanomedicine, 2015)
Along with widespread usage of QDs in electronic and biomedical industries, the likelihood of QDs exposure to the environment and humans is deemed to occur when the QD products are degraded or handled as waste for processing. To date, there are very few toxicological reports available in the literature for non-cadmium QDs in animal models. In this work, we studied the long term in vivo toxicity of InP/ZnS QDs in BALB/c mice. The biodistribution, body weight, hematology, blood biochemistry, and organ histology were determined at a very high dosage (25mg/kg) of InP/ZnS QDs over 84days period. Our results manifested that the QDs formulation did not result in observable toxicity in vivo within the evaluation period, thereby suggesting that the InP/ZnS QDs can be utilized as optical probes or nanocarrier for selected in vivo biological applications when an optimized dosage is employed. This study investigated the toxicity of quantum dots in BALB/c mice, and concluded that no organotoxicity was detectable despite of using high concentration of InP/ZnS quantum dots with prolonged exposure of 3 months. The long term in vivo toxicity of InP/ZnS QDs in BALB/c mice was systematically evaluated in this study. The intact QDs predominantly accumulated in the spleen and liver, and indium element from injected QDs remained in major organs over 84days. No changes in body weight, hematological and biochemical analysis and histological analysis were observed, thereby suggesting that InP/ZnS QDs can serve as optical probes for specific clinical applications when an optimized dosage is employed. [Display omitted]